Poly(o-toluidine dihydrochloride): Spectral Characterization and Synthesis of Eskolite Nanoparticles. Issue 4 (4th March 2017) - Hosny, Nasser Mohammed; Samir, Ghada; Zoromba, Mohamed Shafick; Alghool, Samir
ABSTRACT: Poly( o -toluidine · 2HCl) and its doped polymers with Mn and Cr ions have been synthesized and characterized by FT-IR, UV–Vis. and thermogravimetrical analyses. Potassium dichromate has been used as an initiator and a dopant of chromium in CrPOT preparation. The effect of doping on thermal and optical properties of Poly( o -toluidine dihydrochloride) has been discussed. CrPOT has been used as a precursor of Cr2 O3 nanoparticles through thermal decomposition rout. The obtained nanoparticles have been characterized by X-ray diffraction and high resolution transmission electron microscope. The results indicated that Cr2 O3 exists in hexagonal structure as mesoporous Eskolit with average particle size of 48 nm. Optical band gap measurements indicated that Eskolite nanoparticles have wider band gap than the bulk. GRAPHICAL ABSTRACT: